Pcr-Sscp: A Tool For Molecular Diagnosis Of Leptospirosis - MADHURIMA DE ROY; K.THAVACHELVAM; H.V. BATRA; U. TUTEJA (International Journal of Pharma and Bio Sciences, 2012)
Leptospirosis, a disease with protean manifestations, is caused by Leptospira species. Early and reliable identification of Leptospira serovars remains to be a challenge due to diversity at serovar level. The potential of polymerase chain reaction-single strand conformational polymorphism (PCR-SSCP) was assessed for detection of sequence variation in pathogenic specific 631 bp fragment of 16S rDNA of Leptospira for serovar typing. Standardization of this technique on reference serovars of L. interrogans (Canicola, Pomona and Icterohaemorrhagiae) and of L. borgpetersenii (Ballum, Tarassovi and Javanica) yielded distinct SSCP profiles. Employing this technique 15 isolates could be characterized to serovars Canicola, Icterohaemorrhagiae, Pomona and Javanica. Similar results were obtained when a panel of monoclonal antibodies in ELISA typed these isolates. In addition, this technique was applied on blood samples of human leptospirosis for direct identification and characterization of Leptospira serovars. Five of 50 samples were characterized as serovar Tarassovi. DNA sequencing of 631bp amplicons of these samples validated the results obtained with PCR-SSCP. This PCR-SSCP was therefore, able to identify and characterize the Leptospira to serovar level obviating the need for isolation of leptospires before testing.